(untitled) (Journal of Forest and Livelihood, 2003)
This paper attempts to assess the livelihood impacts of community forestry based on Forest User Groups (FUGs) in the Middle hills of Nepal, using data from the Koshi hills region in the East. The general finding is that impacts are diverse both within and between FUGs, but have been generally positive, in terms of improved levels and security of forest product and benefit flows, various household incomegenerating opportunities, support for community infrastructure and development activities, and improved ‘social capital’ for collective planning and action. Nevertheless, impacts to date are below their potential, and the needs of rural households require more investigation to determine what further opportunities exist and how policy and extension agencies may offer specific needs-oriented support.